Compounds, corrosion inhibitors, and lubricant compositions
The lubricant composition, featuring a compound with an alkali metal and alkylene group, addresses the challenges of stability, low evaporation, and corrosion resistance in space and terrestrial environments, providing effective performance across varying temperatures.
Patent Information
- Application Number
- JP2020218038
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-25
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2040-12-25
AI Technical Summary
Lubricant compositions for space equipment face challenges in maintaining stability, low evaporation, and corrosion resistance in both high vacuum and atmospheric pressure environments, with existing corrosion inhibitors having issues with solubility and evaporation at high temperatures.
A lubricant composition incorporating a compound represented by the general formula (B1), which includes an alkali metal and an alkylene group, providing excellent solubility, metal corrosion resistance, and stability under high temperature environments, along with an ionic liquid and a corrosion inhibitor.
The lubricant composition achieves enhanced stability, low evaporation, and improved metal corrosion resistance across a wide range of temperatures and environments, making it suitable for both space applications and normal conditions.
Smart Images

Figure 0007655724000028 
Figure 0007655724000029 
Figure 0007655724000030
Abstract
Description
[Technical field]
[0001] The present invention relates to compounds, corrosion inhibitors, and lubricant compositions. [Background technology]
[0002] Unlike the Earth's environment, outer space has no atmosphere, so there is no atmospheric pressure and it is an extremely high vacuum environment. In such a high vacuum, liquids with high vapor pressure will evaporate during use, making it difficult to use them for long periods in outer space. Also, unlike the Earth's surface, which has an atmosphere, the effects of thermal radiation and heat emission from the sun are large, so the surface temperatures of devices used in outer space, such as artificial satellites, probes, and lunar vehicles, will range from below freezing to high temperatures. Therefore, since these devices are exposed to harsh environments different from those on Earth, in order to keep the devices mounted on the devices operating smoothly for a long period of time, there is a demand for lubricant compositions that can be used under high vacuum, low temperature environments below freezing, and high temperature environments of 200 to 300°C.
[0003] Furthermore, lubricant compositions for lubricating equipment installed in space devices are required to have a reduced coefficient of friction (lubricity) and to maintain lubricity for a long period of time (low volatility). For this reason, MAC oils (cyclopentane oils such as tris(2-octyldodecyl)cyclopentane) and PFAEs (perfluoroalkyl ethers), which have low vapor pressure, are used as the main base oils. However, MAC oils have a problem in that their viscosity changes significantly with temperature due to their low viscosity index, and PFAEs have a problem in that they have insufficient lubrication properties. In recent years, therefore, research has been conducted into the use of ionic liquids, which have excellent low-temperature fluidity, low volatility under high vacuum, and lubricity, as the main component of lubricant compositions for space equipment (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-36294 A Summary of the Invention [Problem to be solved by the invention]
[0005] From the viewpoint of recyclability of space equipment, it is required that the above-mentioned equipment, after being used in the space environment, be returned to Earth for long-term storage and maintenance, and then be able to be taken out into the space environment again for use. Therefore, lubricant compositions for space equipment are required to have excellent stability and low volatility not only in the space environment but also in the atmospheric pressure environment after returning to Earth, i.e., under normal temperature and pressure conditions. However, although ionic liquids have excellent lubricity in the space environment, they have the problem that they are prone to absorbing moisture and oxygen under atmospheric pressure and can corrode metals depending on the material.
[0006] Therefore, corrosion inhibitors capable of suppressing the corrosiveness of metals caused by ionic liquids have been investigated. However, corrosion inhibitors that have been conventionally used in mineral oils and the like have low solubility in ionic liquids, and therefore cannot be applied to ionic liquids. In addition, in the technology described in Patent Document 1, a fatty acid amine salt is used as a rust inhibitor to suppress the generation of rust caused by the ionic liquid. However, the fatty acid amine salt described in Patent Document 1 has a problem in that it evaporates at high temperatures.
[0007] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a compound and a corrosion inhibitor that are excellent in stability under high vacuum, low temperature environments, high temperature environments, normal temperature environments, and normal pressure environments, and further a lubricant composition that contains the corrosion inhibitor and has excellent metal corrosion resistance, solubility, and low evaporation properties. [Means for solving the problem]
[0008] Means for Solving the Problems The present inventors have conducted extensive research and found that a specific compound can solve the above problems, thereby completing the present invention.
[0009] That is, the present invention provides the following [1]. [1] A compound represented by the following general formula (B1): [ka] [In the general formula (B1), M represents an alkali metal; R B11 represents an alkylene group having 1 to 19 carbon atoms. Effect of the Invention
[0010] According to the present invention, it is possible to provide a compound and a corrosion inhibitor that are excellent in stability under high vacuum, low temperature environments, high temperature environments, room temperature environments, and normal pressure environments, as well as a lubricant composition that contains the corrosion inhibitor and has excellent metal corrosion resistance, solubility, and low evaporation properties. [Brief description of the drawings]
[0011] [Figure 1] 1 is a 1H-NMR chart of the corrosion inhibitor (B1-1) used in Examples 1 and 2. [Diagram 2] 1 is a 1H-NMR chart of the corrosion inhibitor (B1-2) used in Example 3. [Diagram 3] 1 is a 1H-NMR chart of the corrosion inhibitor (B1-3) used in Example 4. [Figure 4] 1 is a 1H-NMR chart of the corrosion inhibitor (B1-4) used in Example 5. [Diagram 5] 1 is a 1H-NMR chart of the corrosion inhibitor (B1-5) used in Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In this specification, the lower limit and upper limit described in stages for the preferred numerical range (for example, the range of the content, etc.) can be combined independently. For example, from the description of the lower limit of "preferably 10 or more, more preferably 30 or more, and even more preferably 40 or more" and the description of the upper limit of "preferably 90 or less, more preferably 80 or less, and even more preferably 70 or less", it is also possible to select a range combining the lower limit and upper limit independently selected, such as "10 or more and 70 or less", "30 or more and 70 or less", and "40 or more and 80 or less". From the same description, it is also possible to select a range simply defining either the lower limit or the upper limit, such as "40 or more" or "70 or less". The same is true for the suitable range that can be selected from the description of "preferably 10 or more and 90 or less, more preferably 30 or more and 80 or less, and even more preferably 40 or more and 70 or less", "preferably 10 to 90, more preferably 30 to 80, and even more preferably 40 to 70". In the present specification, in the description of a numerical range, for example, "10 to 90" is synonymous with "10 or more and 90 or less." In the description of a numerical range, the numerical values of "greater than or equal to," "less than or equal to," "less than," and "greater than" can also be arbitrarily combined. In this specification, for example, "(meth)acrylate" is used as a term indicating both "acrylate" and "methacrylate", and the same applies to other similar terms and similar labels.
[0013] The compound of this embodiment is a compound represented by the following general formula (B1). [ka] [In the general formula (B1), M represents an alkali metal; R B11 represents an alkylene group having 1 to 19 carbon atoms.
[0014] In order to solve the above problems, the inventors conducted extensive research and found that by using a compound that has the same type of cation and anion structure as an ionic liquid and has an alkyl carboxylate metal salt on the side chain of the cation, it is possible to achieve both solubility in ionic liquids, resistance to metal corrosion, and stability in high-temperature environments. Based on these findings, the present inventors conducted further intensive research and completed the present invention.
[0015] [Compound] The compound of this embodiment is a compound represented by the following general formula (B1). [ka] [In the general formula (B1), M represents an alkali metal; R B11 represents an alkylene group having 1 to 19 carbon atoms.
[0016] Examples of the alkali metal of M in the general formula (B1) include sodium, potassium, etc. Among these, sodium is preferable from the viewpoints that when a differential thermal analyzer is used under normal pressure environment, the temperature is raised from 20° C. in a nitrogen atmosphere at a rate of 10° C. / min, the temperature at which the mass is reduced by 5% from the initial mass (5% mass reduction temperature) is higher, and that it is stable even under high temperature environment.
[0017] R in the general formula (B1) B11 The alkylene group having 1 to 19 carbon atoms may be linear or branched. B11 The number of carbon atoms in R is preferably 3 to 17, more preferably 5 to 15, even more preferably 7 to 12, and still more preferably 8 to 10. B11 When the carbon number of R is within the above range, it can be applied in a wide range of fields such as lubricant compositions and grease compositions. B11 When the carbon number of R is 5 or more, the solubility in the ionic liquid is easily improved. B11 When the carbon number of R is 8 or more, the metal corrosion resistance is easily improved. B11When the carbon number is 15 or less, the 5% mass loss temperature is easily increased, and stability in a high-temperature environment is easily improved.
[0018] The compound represented by the general formula (B1) can be synthesized, for example, by the following synthesis method. First, put N-methylpyrrolidine, Br-R into a 300 mL flask. B11 -COO-C2H5(R B11 A compound represented by the formula (I) (C1-C19 alkylene group) and isopropanol are added and reacted at 50°C to 70°C for 7 to 9 hours. Ethyl acetate is added to this reaction mixture, and the precipitate is washed with hexane several times, and then dried with a vacuum pump for several hours to obtain a white solid. The obtained white solid is diluted with methylene chloride, and lithium bis(trifluoromethanesulfonyl)amide and water are added, and reacted at 10°C to 30°C for 0.5 to 2 hours. Next, the organic layer is separated, washed with water several times, and then concentrated with an evaporator to obtain a reaction product. Methanol, water, and an alkali metal hydroxide are added to the obtained reaction product, and reacted at 90°C to 110°C for 0.5 to 2 hours, and the reaction mixture is concentrated with an evaporator to obtain a compound represented by the general formula (B1). The compound represented by the general formula (B1) is, for example, 1 The structure can be analyzed using H-NMR under the conditions described in the Examples.
[0019] [Stability in high temperature environments (5% mass loss temperature)] The 5% mass loss temperature of the compound represented by the general formula (B1) is preferably 270° C. or higher, more preferably 300° C. or higher, and even more preferably 310° C. or higher, thereby providing excellent stability even in a high-temperature environment. The 5% mass loss temperature can be measured by the method described in the Examples.
[0020] <Corrosion inhibitor (B)> The compound represented by the general formula (B1) has excellent resistance to metal corrosion and can be used as a corrosion inhibitor (B) in the lubricant composition described below. The corrosion inhibitor (B) includes at least one compound selected from the compounds represented by the above general formula (B1). The content of the compound represented by general formula (B1) is preferably 60 mass% to 100 mass%, more preferably 70 mass% to 100 mass%, and even more preferably 80 mass% to 100 mass%, based on the total amount of the corrosion inhibitor (B).
[0021] [Lubricant composition] The lubricant composition of this embodiment contains an ionic liquid (A) and a corrosion inhibitor (B) containing one or more compounds selected from the compounds represented by the above-mentioned general formula (B1).
[0022] In the following description, the ionic liquid (A) and the corrosion inhibitor (B) will also be referred to as component (A) and component (B), respectively.
[0023] In the lubricant composition of this embodiment, the total content of component (A) and component (B) is preferably 70 mass % or more, more preferably 80 mass % or more, even more preferably 90 mass % or more, and still more preferably 95 mass % or more. In the lubricant composition of this embodiment, the upper limit of the total content of components (A) and (B) may be 100% by mass. However, when the lubricant composition contains components other than components (A) and (B), the upper limit of the total content of components (A) and (B) may be adjusted in relation to the other components, and is preferably 99% by mass or less, more preferably 98% by mass or less.
[0024] In the lubricant composition of this embodiment, from the viewpoint of making it easier to exhibit the effects of solubility in the ionic liquid (A) and metal corrosion resistance, the content of the compound represented by the general formula (B1) is preferably from 0.01 to 10 mass%, more preferably from 0.1 to 10 mass%, even more preferably from 0.1 to 5.0 mass%, still more preferably from 1.0 to 3.0 mass%, and even more preferably from 1.5 to 2.5 mass%, based on the total amount (100 mass%) of the lubricant composition. In addition, in the lubricant composition of this embodiment, the content of the corrosion inhibitor (B) is, from the viewpoint of making it easier to exhibit the effects of solubility in the ionic liquid (A) and metal corrosion resistance, preferably from 0.01 mass % to 10 mass %, more preferably from 0.1 mass % to 10 mass %, even more preferably from 0.1 mass % to 5.0 mass %, still more preferably from 1.0 mass % to 3.0 mass %, and even more preferably from 1.5 mass % to 2.5 mass %, based on the total amount (100 mass %) of the lubricant composition. The corrosion inhibitor (B) may be used alone or in combination of two or more. When two or more types are used, the preferred total content is the same as the above content.
[0025] Each component contained in the lubricant composition of the present embodiment will be described below.
[0026] <Ionic liquid (A)> The lubricant composition of the present embodiment contains an ionic liquid (A). The ionic liquid (A) is a liquid compound composed of cations and anions. The anion of the ionic liquid (A) preferably contains bis(trifluoromethanesulfonyl)amide.
[0027] The cation of the ionic liquid (A) preferably contains a cation represented by the following general formula (A1). [ka] [In the above general formula (A1), n is 1 or 2, X is a methylene group or oxygen, and R A11 , R A12 are each independently a group selected from an alkyl group having 1 to 12 carbon atoms which may have an ether group, an ester group, a nitrile group, or a silyl group.
[0028] R in general formula (A1) A11 , R A12The alkyl group preferably has 1 to 6 carbon atoms, and more preferably 1 to 4 carbon atoms, from the viewpoint of reducing the viscosity of the ionic liquid and improving its stability in a high-temperature environment. R A11 As the alkyl group, a methyl group is preferable. A12 As the alkyl group, an n-butyl group and a methoxyethyl group are preferable.
[0029] Examples of the cation represented by the general formula (A1) include 1-butyl-1-methylpyrrolidinium, 1-pentyl-1-methylpyrrolidinium, 1-hexyl-1-methylpyrrolidinium, 1-heptyl-1-methylpyrrolidinium, 1-octyl-1-methylpyrrolidinium, 1-nonyl-1-methylpyrrolidinium, 1-decyl-1-methylpyrrolidinium, 1-undecyl-1-methylpyrrolidinium, 1-dodecyl-1-methylpyrrolidinium, 1-methoxymethyl-1-methylpyrrolidinium, 1-(2-methoxyethyl)- 1-Methylpyrrolidinium, 1-(2-methoxy-2-oxoethyl)-1-methylpyrrolidinium, 1-cyanomethyl-1-methylpyrrolidinium, 1-trimethylsilylmethyl-1-methylpyrrolidinium, 1-butyl-1-methylpiperidinium, 1-pentyl-1-methylpiperidinium, 1-hexyl-1-methylpiperidinium, 1-heptyl-1-methylpiperidinium, 1-octyl-1-methylpiperidinium, 1-nonyl-1-methylpiperidinium, 1-decyl-1-methylpiperidinium, 1-undecyl-1 -methylpiperidinium, 1-dodecyl-1-methylpiperidinium, 1-methoxymethyl-1-methylpiperidinium, 1-(2-methoxyethyl)-1-methylpiperidinium, 1-(2-methoxy-2-oxoethyl)-1-methylpiperidinium, 1-cyanomethyl-1-methylpiperidinium, 1-trimethylsilylmethyl-1-methylpiperidinium, 1-butyl-1-methylmorpholinium, 1-pentyl-1-methylmorpholinium, 1-hexyl-1-methylmorpholinium, 1-heptyl-1-methylmorpholinium morpholinium, 1-octyl-1-methylmorpholinium, 1-nonyl-1-methylmorpholinium, 1-decyl-1-methylmorpholinium, 1-undecyl-1-methylmorpholinium, 1-dodecyl-1-methylmorpholinium, 1-(2-methoxyethyl)-1-methylmorpholinium, 1-methoxymethyl-1-methylmorpholinium, 1-(2-methoxy-2-oxoethyl)-1-methylmorpholinium, 1-cyanomethyl-1-methylmorpholinium, 1-trimethylsilylmethyl-1-methylmorpholinium, and the like. Among these, from the viewpoint of reducing the viscosity of the ionic liquid (A) and improving stability in a high-temperature environment, preferred are 1-butyl-1-methylpyrrolidinium, 1-pentyl-1-methylpyrrolidinium, 1-hexyl-1-methylpyrrolidinium, 1-(2-methoxyethyl)-1-methylpyrrolidinium, 1-butyl-1-methylpiperidinium, 1-(2-methoxyethyl)-1-methylpiperidinium, and 1-(2-methoxyethyl)-1-methylmorpholinium, more preferably 1-butyl-1-methylpyrrolidinium, 1-(2-methoxyethyl)-1-methylpyrrolidinium, and 1-(2-methoxyethyl)-1-methylpiperidinium, and even more preferably 1-butyl-1-methylpyrrolidinium and 1-(2-methoxyethyl)-1-methylpyrrolidinium.
[0030] The ionic liquid (A) preferably contains at least one selected from a compound represented by the following general formula (A2) and a compound represented by the following general formula (A3).
[0031] [ka] [In the above general formula (A2), n is 1 or 2, X is a methylene group or oxygen, and R A21 represents an alkyl group having 2 to 12 carbon atoms.]
[0032] [ka] [In the above general formula (A3), n is 1 or 2, X is a methylene group or oxygen, and R A31 represents an alkylene group having 1 to 5 carbon atoms, R A32 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms.]
[0033] In the general formula (A2), R A21 The number of carbon atoms in R is preferably 2 to 8, and more preferably 3 to 6. A21When the carbon number of R is 2 or more, the side chain can move freely and the symmetry is low, so that crystallization is suppressed and the function as an ionic liquid can be improved. A21 When the number of carbon atoms is 12 or less, the side chain does not become too large and the compound as a whole has high ionicity, making it easy to suppress oxidative deterioration.
[0034] In the general formula (A3), R A31 The number of carbon atoms in R is preferably 1 to 3, and more preferably 1 to 2. A32 The number of carbon atoms in R is preferably 1 to 2. A31 When the carbon number of R is 1 or more, the side chain can move freely and the symmetry is low, so that crystallization is suppressed and the function as an ionic liquid can be improved. A31 or R A32 When the number of carbon atoms is 3 or less, the side chain does not become too large and the compound as a whole has high ionicity, making it easy to suppress oxidative deterioration.
[0035] The content of the compound represented by general formula (A2) is preferably 60% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and even more preferably 80% by mass to 100% by mass, based on the total amount of the ionic liquid (A). The content of the compound represented by general formula (A3) is preferably 60% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and even more preferably 80% by mass to 100% by mass, based on the total amount of the ionic liquid (A).
[0036] The ionic liquid (A) preferably has a kinetic viscosity of 2.0 mm at 40° C. from the viewpoints of low volatility and suppression of power loss due to viscous resistance. 2 / s~100.0mm 2 / s, more preferably 10.0 mm 2 / s~70.0mm 2 / s, and more preferably 20.0 mm 2 / s~40.0mm 2 / s. The 100°C kinetic viscosity of the ionic liquid (A) is preferably 1.0 mm from the viewpoint of low volatility and suppression of power loss due to viscous resistance. 2 / s~20.0mm 2 / s, more preferably 2.0 mm 2 / s~10.0mm 2 / s, more preferably 3.0 mm 2 / s~7.0mm 2 / s. The viscosity index of the ionic liquid (A) is preferably 100 or more, more preferably 120 or more, and even more preferably 140 or more, from the viewpoint of minimizing viscosity changes even when used in a space environment where the temperature range changes greatly between low and high temperatures. The 40° C. kinematic viscosity, the 100° C. kinematic viscosity, and the viscosity index can be measured or calculated in accordance with JIS K 2283:2000. Furthermore, when the ionic liquid (A) is a mixture of two or more types of ionic liquids, the kinematic viscosity and viscosity index of the mixture preferably fall within the above ranges.
[0037] The pour point of the ionic liquid (A) is preferably 0° C. or lower, more preferably −10° C. or lower, and even more preferably −20° C. or lower, from the viewpoint of suppressing an increase in viscous resistance at low temperatures. The pour point of the ionic liquid (A) can be measured in accordance with JIS K 2269:1987.
[0038] From the viewpoint of metal corrosion resistance, the acid value of the ionic liquid (A) is preferably 1 mgKOH / g or less, more preferably 0.5 mgKOH / g or less, and even more preferably 0.3 mgKOH / g or less.
[0039] The flash point of the ionic liquid (A) is preferably 200° C. or higher, more preferably 250° C. or higher, and even more preferably 300° C. or higher, from the viewpoint of low volatility.
[0040] The ion concentration of the ionic liquid (A) measured at 15° C. is preferably 1.0 mol / dm 3 More preferably, 1.5 mol / dm 3More preferably, 2.0 mol / dm 3 That's all. Here, the ion concentration is defined as the density (g / cm) measured at 15°C in the ionic liquid. 3 ) / molecular weight Mw (g / mol)] × 1000. 3 If the content is more than this, it is possible to further improve low volatility and stability in a high temperature environment.
[0041] The molecular weight of the ionic liquid (A) is preferably from 410 to 570, more preferably from 410 to 470, and even more preferably from 420 to 440. When the molecular weight of the ionic liquid (A) is within this range, the charge density and the alkyl chain length of the cation fall within appropriate ranges, and it is possible to reduce the viscosity of the ionic liquid and improve its stability in a high-temperature environment.
[0042] In the lubricant composition of the present embodiment, the content of the ionic liquid (A) is not particularly limited, but from the viewpoint of making it easier to exhibit the effects of the present invention, it is preferably 60 mass% to 99.5 mass%, more preferably 70 mass% to 99.0 mass%, and even more preferably 80 mass% to 98.5 mass% based on the total amount (100 mass%) of the lubricant composition.
[0043] The lubricant composition of this embodiment may contain other components (e.g., ethyl acetate, etc.) in addition to the ionic liquid (A) described above. From the viewpoint of fully exerting the effects of the present invention, the content of the ionic liquid (A) described above is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 90 mass% or more, and even more preferably 100 mass% based on the total amount of the ionic liquid.
[0044] The ratio (B1 / A) of the content of the compound represented by the general formula (B1) to the content of the ionic liquid (A) is preferably 0.0005 or more and 0.15 or less, more preferably 0.001 or more and 0.111 or less, and even more preferably 0.005 or more and 0.08 or less, in terms of mass ratio. When (B1 / A) is 0.0005 or more, it is easy to make the metal corrosion resistance sufficient. When (B1 / A) is 0.15 or less, it is easy to make the solubility in the ionic liquid (A) sufficient.
[0045] <Other ingredients> The lubricant composition of the present embodiment may contain other components besides the above-mentioned components, as necessary, within the range that does not impair the effects of the present invention. The other components include, for example, a viscosity index improver. These may be used alone or in combination of two or more.
[0046] - Viscosity index improver - By including a viscosity index improver in the lubricant composition of the present embodiment, the viscosity index of the lubricant composition can be improved, and thus the change in viscosity can be reduced even when the lubricant composition is used in a space environment where the temperature range changes greatly between low and high temperatures.
[0047] Examples of the viscosity index improver include polymers such as non-dispersed poly(meth)acrylate and dispersed poly(meth)acrylate, which are soluble in the ionic liquid. These may be used alone or in combination of two or more. The mass average molecular weight (Mw) of these viscosity index improvers is usually 5,000 to 1,000,000, preferably 6,000 to 100,000, and more preferably 10,000 to 50,000, but is appropriately set depending on the type of polymer. In this specification, the mass average molecular weight (Mw) of each component is a value calculated in terms of standard polystyrene as measured by gel permeation chromatography (GPC).
[0048] The contents of the above-mentioned other components can be appropriately adjusted within a range that does not impair the effects of the present invention, and each of them is usually 0.001 mass% to 15 mass%, preferably 0.005 mass% to 10 mass%, more preferably 0.01 mass% to 7 mass%, and even more preferably 0.03 mass% to 5 mass%, based on the total amount (100 mass%) of the lubricant composition. In this specification, the additives as the other components may be mixed with other components in the form of a solution diluted and dissolved in a part of the ionic liquid (A) in consideration of handling properties, solubility in the ionic liquid (A), etc. In such a case, in this specification, the content of the additives as the other components means the content in terms of active ingredients (resin content) excluding the diluent.
[0049] [Physical properties of lubricant composition] <Kinematic viscosity at 40°C, kinematic viscosity at 100°C, and viscosity index>
[0050] The 40° C. kinetic viscosity of the lubricant composition of this embodiment is preferably 2.0 mm from the viewpoint of low volatility and suppression of power loss due to viscous resistance. 2 / s~100.0mm 2 / s, more preferably 10.0 mm 2 / s~70.0mm 2 / s, and more preferably 20.0 mm 2 / s~50.0mm 2 / s. The 100°C kinetic viscosity of the lubricant composition of this embodiment is preferably 1.0 mm from the viewpoint of low volatility and suppression of power loss due to viscous resistance. 2 / s~20.0mm 2 / s, more preferably 2.0 mm 2 / s~15.0mm 2 / s, more preferably 3.0 mm 2 / s~10.0mm 2 / s. The viscosity index of the lubricant composition of this embodiment is preferably 100 or more, more preferably 120 or more, and even more preferably 140 or more, from the viewpoint of minimizing viscosity change even when used in a space environment where the temperature range changes greatly between low and high temperatures. The 40° C. kinematic viscosity, the 100° C. kinematic viscosity, and the viscosity index can be measured or calculated in accordance with JIS K 2283:2000.
[0051] <Solubility (appearance)> It is preferable that the corrosion inhibitor (B) dissolves in the ionic liquid (A) and becomes colorless and transparent. This can be determined by the method described in the Examples.
[0052] <Low volatility (amount of evaporation)> The amount of evaporation is preferably less than 0.1% by mass, and can be measured by the method described in the Examples.
[0053] <Metal corrosion resistance> With regard to the metal corrosion resistance, it is preferable that no corrosion is observed when judged by the method described in the examples.
[0054] [Uses of lubricant composition] The lubricant composition of the present embodiment has excellent metal corrosion resistance, solubility, and low evaporation properties not only under high vacuum, low temperature, and high temperature environments, but also under normal temperature and pressure environments, and therefore can be suitably used in devices mounted on devices used in outer space, such as artificial satellites, probes, and lunar vehicles. In addition, since the lubricant composition of the present embodiment is excellent for use under high vacuum, it can be suitably used in manufacturing devices for semiconductors, liquid crystal and organic EL flat panel displays, solar cell panels, and the like. The lubricant composition of the present embodiment is suitable for use as a lubricant composition for devices used in space, but may also be used in other applications.
[0055] [Method of manufacturing lubricant composition] In this embodiment, there is provided a method for producing a lubricant composition, which includes a step of mixing an ionic liquid (A) with a compound represented by the following general formula (B1). [ka] [In the general formula (B1), M represents an alkali metal; R B11 represents an alkylene group having 1 to 19 carbon atoms.
[0056] The method for mixing the above components is not particularly limited, but may be, for example, a step of adding a compound represented by the following general formula (B1) to the ionic liquid (A) and then mixing them. The manufacturing method may further include the step of adding the other components described above.
[0057] [Grease composition] The lubricant composition of this embodiment can also be used as a grease composition by containing the ionic liquid (A), the corrosion inhibitor (B), and a thickener. Since outer space is a microgravity environment, the gravity supply method of lubricant commonly used on Earth cannot be applied. However, by applying the lubricant composition of the present embodiment to a grease composition, lubricity can be maintained without supplying the lubricant during use.
[0058] As a thickener for the grease composition, cellulose nanofibers can be suitably used. Since both the ionic liquid (A) and the cellulose nanofibers are hydrophilic, the ionic liquid (A) and the corrosion inhibitor (B) can be retained in the cellulose nanofibers with good affinity. The grease composition may contain components other than the components (A) and (B) as long as the effects of the present invention are not impaired.
[0059] <Nanofiber> The nanofibers contained in the grease composition of the present embodiment are preferably one or more types selected from cellulose nanofibers and hydrophilic modified cellulose nanofibers. By including nanofibers in the grease composition, the nanofibers are uniformly dispersed in the grease composition to form a higher-order structure. Since the nanofibers have excellent mechanical stability, the higher-order structure formed by the nanofibers is stable against shear. As a result, the shear stability of the grease composition is improved, and the leakage prevention performance of the grease is improved. Even if the nanofiber content is small, the proportion of the ionic liquid (A) in the grease composition can be increased by adjusting the worked penetration of the grease composition to an appropriate range, which increases the lubricity of the grease composition and also makes it easier to improve the wear resistance.
[0060] (Cellulose nanofiber) Cellulose nanofiber refers to a fibrous material with a thickness of 500 nm or less that is produced by defibrating plant fibers to the nano level, and is distinct from flake-like, powder-like, and particulate materials. Lignocellulose can also be used as a raw material for cellulose nanofibers. Lignocellulose is a complex hydrocarbon polymer that constitutes the cell walls of plants and is known to be composed mainly of the polysaccharides cellulose and hemicellulose and the aromatic polymer lignin. The cellulose constituting the cellulose nanofiber may be one or more selected from lignocellulose and acetylated lignocellulose. The cellulose nanofiber may also contain one or more selected from hemicellulose and lignin. Furthermore, the cellulose constituting the cellulose nanofiber may be chemically bonded to one or more selected from hemicellulose and lignin. The degree of polymerization of the cellulose constituting the cellulose nanofibers is preferably 50-3,000, more preferably 100-1,500, even more preferably 150-1,000, and even more preferably 200-800. In this specification, the degree of polymerization of cellulose means a value measured by a viscosity method.
[0061] (Hydrophilic modified cellulose nanofiber) The hydrophilic modified cellulose nanofibers are cellulose nanofibers that have been subjected to a modification treatment to the extent that the hydrophilicity can be maintained. Specific examples of the modification treatment include esterification such as acetylation, phosphorylation, urethanization, carbamidation, etherification, carboxymethylation, TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl radical) oxidation, and periodate oxidation. The modified cellulose nanofibers used in the present invention may be subjected to only one of these modification treatments, or may be subjected to two or more of them.
[0062] According to one aspect of the present invention, the following [1] to [7] are provided. [1] A compound represented by the following general formula (B1): [ka] [In the general formula (B1), M represents an alkali metal; R B11 represents an alkylene group having 1 to 19 carbon atoms. [2] A corrosion inhibitor comprising one or more compounds selected from the compounds described in [1] above. [3] A lubricant composition comprising an ionic liquid (A) and the corrosion inhibitor (B) described in [2] above. [4] The lubricant composition according to the above [3], wherein the ionic liquid (A) contains a cation represented by the following general formula (A1): [ka] [In the above general formula (A1), n is 1 or 2, X is a methylene group or oxygen, and R A11 , R A12 are each independently a group selected from an alkyl group having 1 to 12 carbon atoms which may have an ether group, an ester group, a nitrile group, or a silyl group. [5] The lubricant composition according to the above [3] or [4], wherein the ionic liquid (A) comprises at least one compound selected from the group consisting of a compound represented by the following general formula (A2) and a compound represented by the following general formula (A3): [ka] [In the above general formula (A2), n is 1 or 2, X is a methylene group or oxygen, and R A21 represents an alkyl group having 2 to 12 carbon atoms.] [ka] [In the above general formula (A3), n is 1 or 2, X is a methylene group or oxygen, and R A31 represents an alkylene group having 1 to 5 carbon atoms, R A32 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms.] [6] The lubricant composition according to any one of the above [3] to [5], wherein the content of the compound represented by general formula (B1) is 0.1 mass % or more and 10 mass % or less, based on the total amount of the lubricant composition. [7] The lubricant composition according to any one of the above [3] to [6], wherein the ratio (B1 / A) of the content of the compound represented by general formula (B1) to the content of the ionic liquid (A) is, in mass ratio, 0.0005 or more and 0.15 or less. EXAMPLES
[0063] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to the following examples.
[0064] The structure of each corrosion inhibitor described below was analyzed by the following method.
[0065] [NMR structure analysis] Regarding the corrosion inhibitors (B1-1) to (B1-5) described below, 1 The measurements were performed using H-NMR under the following conditions. 1 H-NMR charts are shown in Figs. 1 to 5. Device name: JNM-ECZ400S (manufactured by JEOL Ltd.) ·Measurement temperature: 20℃ ·Reference material: DMSO-D6
[0066] [Synthesis and acquisition of corrosion inhibitor (B)] Corrosion inhibitors (B1-1) to (B1-5) and corrosion inhibitor (B2-2) were synthesized by the methods described below. Corrosion inhibitors (B2-1) and (B2-3) were also obtained.
[0067] <Corrosion inhibitor (B1-1)> Corrosion inhibitors (B1-1) First, N-methylpyrrolidine (2.44 g, 28.6 mmol), ethyl 10-bromodecanoate (8.80 g, 31.5 mmol), and 20 mL of isopropanol were added to a 300 mL flask and reacted at 60 ° C for 8 hours. 100 mL of ethyl acetate was added to this reaction mixture, and the precipitate was washed with hexane several times, and then dried with a vacuum pump for several hours to obtain 9.5 g of a white solid. The obtained white solid was diluted with 100 mL of methylene chloride, and lithium bis(trifluoromethanesulfonyl)amide (8.21 g, 28.6 mmol) and 100 mL of water were added, and the mixture was reacted at 20 ° C for 1 hour. Next, the organic layer was separated, washed with water several times, and then concentrated with an evaporator to obtain 14.1 g of the reaction product. To the obtained reaction product, 16 mL of methanol, 2 mL of water, and sodium hydroxide (1.00 g, 25.0 mmol) were added, and the mixture was reacted at 100° C. for 1 hour. The reaction mixture was concentrated with an evaporator to obtain a corrosion inhibitor (B1-1). The obtained corrosion inhibitor (B1-1) weighed 13.57 g and was 24.3 mmol. The obtained corrosion inhibitor (B1-1) had a 5% mass loss temperature of 317° C. The structure of the corrosion inhibitor (B1-1) is shown in structural formula (B1-1).
[0068] [ka]
[0069] <Corrosion inhibitor (B1-2)> Corrosion inhibitors (B1-2) A corrosion inhibitor (B1-2) was obtained by synthesizing the corrosion inhibitor (B1-1) in the same manner as in the synthesis of the corrosion inhibitor (B1-1), except that ethyl 11-bromoundecanoate (9.24 g, 31.5 mmol) was used instead of ethyl 10-bromodecanoate. The obtained corrosion inhibitor (B1-2) had a weight of 13.63 g and a weight of 23.8 mmol. The obtained corrosion inhibitor (B1-2) had a 5% mass loss temperature of 314° C. The structure of the corrosion inhibitor (B1-2) is shown in structural formula (B1-2).
[0070] [ka]
[0071] <Corrosion inhibitor (B1-3)> Corrosion inhibitors (B1-3) A corrosion inhibitor (B1-3) was obtained by synthesizing the corrosion inhibitor (B1-3) in the same manner as in the synthesis of the corrosion inhibitor (B1-1), except that potassium hydroxide (1.40 g, 25.0 mmol) was used instead of sodium hydroxide. The obtained corrosion inhibitor (B1-3) weighed 13.51 g and was 23.5 mmol. The obtained corrosion inhibitor (B1-3) had a 5% mass loss temperature of 280° C. The structure of the corrosion inhibitor (B1-3) is shown in structural formula (B1-3).
[0072] [ka]
[0073] <Corrosion inhibitor (B1-4)> Corrosion inhibitors (B1-4) A corrosion inhibitor (B1-4) was obtained by synthesizing in the same manner as in the synthesis of the corrosion inhibitor (B1-1), except that ethyl 6-bromohexanoate (7.03 g, 31.5 mmol) was used instead of ethyl 10-bromodecanoate. The obtained corrosion inhibitor (B1-4) weighed 12.57 g and was 25.0 mmol. The obtained corrosion inhibitor (B1-4) had a 5% mass loss temperature of 291° C. The structure of the corrosion inhibitor (B1-4) is shown in structural formula (B1-4).
[0074] [ka]
[0075] <Corrosion inhibitor (B1-5)> Corrosion inhibitors (B1-5) A corrosion inhibitor (B1-5) was obtained by synthesizing the corrosion inhibitor (B1-1) in the same manner as above, except that ethyl 8-bromooctanoate (7.91 g, 31.5 mmol) was used instead of ethyl 10-bromodecanoate. The obtained corrosion inhibitor (B1-5) weighed 13.16 g and was 24.8 mmol. The obtained corrosion inhibitor (B1-5) had a 5% mass loss temperature of 318° C. The structure of the corrosion inhibitor (B1-5) is shown in structural formula (B1-5).
[0076] [ka]
[0077] <Corrosion inhibitor (B2-1)> Corrosion inhibitor (B2-1): Disodium sebacate Disodium sebacate (Tokyo Chemical Industry Co., Ltd.) was obtained and used as a corrosion inhibitor (B2-1). The corrosion inhibitor (B2-1) had a 5% mass loss temperature of 381° C. The structure of the corrosion inhibitor (B2-1) is shown in structural formula (B2-1).
[0078] [ka]
[0079] <Corrosion inhibitor (B2-2)> Corrosion inhibitor (B2-2): Bis(tetramethylammonium) decanedioate Decanedioic acid (27.7 g, 0.137 mol) and tetramethylammonium hydroxide (approximately 25% aqueous solution, 100 g, 0.274 mol) were added to a 500 mL flask and reacted at room temperature (20° C.) for 1 hour. The reaction mixture was concentrated using a rotary evaporator, and the resulting solid was dried using a vacuum pump for several hours to obtain a corrosion inhibitor (B2-2). The obtained corrosion inhibitor (B2-2) weighed 47.4 g and was 0.136 mol. The obtained corrosion inhibitor (B2-2) had a 5% mass loss temperature of 200° C. The structure of the corrosion inhibitor (B2-2) is shown in structural formula (B2-2).
[0080] [ka]
[0081] <Corrosion inhibitors (B2-3)> Corrosion inhibitors (B2-3) A product name: Killeslite T (manufactured by Killest Co., Ltd.) was obtained and used as a corrosion inhibitor (B2-3). The corrosion inhibitor (B2-3) had a 5% mass loss temperature of 130°C.
[0082] The corrosion inhibitors thus obtained were evaluated as follows, and the results are shown in Table 1.
[0083] [Evaluation of stability in high temperature environments (5% mass loss temperature)] For each of the corrosion inhibitors (B1-1) to (B1-5) and the corrosion inhibitors (B2-1) to (B2-3), a differential thermal analyzer was used under normal pressure to measure the temperature at which the mass decreased by 5% from the initial mass (5% mass loss temperature) by increasing the temperature from 20°C in a nitrogen atmosphere at a rate of 10°C / min.
[0084] [Table 1]
[0085] As can be seen from Table 1, the corrosion inhibitors (B1-1) to (B1-5) which satisfy all of the configurations of the present invention have a 5% mass loss temperature of 270° C. or higher, which is sufficiently high, and are stable even in high-temperature environments. On the other hand, the corrosion inhibitor (B2-1) had a 5% mass loss temperature of 270°C or higher, but the corrosion inhibitors (B2-2) to (B2-3) had a 5% mass loss temperature of less than 270°C. Therefore, the corrosion inhibitors (B2-2) to (B2-3) may not be usable in the high-temperature space environment.
[0086] Next, lubricant compositions were prepared using the above-mentioned corrosion inhibitors (B1-1) to (B1-5) and the corrosion inhibitors (B2-1) to (B2-3) by the method described below. The physical properties of each lubricant composition were measured or calculated by the following methods.
[0087] [Kinematic viscosity at 40°C, kinematic viscosity at 100°C, and viscosity index] The 40° C. kinematic viscosity, 100° C. kinematic viscosity and viscosity index of the lubricant composition and the ionic liquid (A) were measured or calculated in accordance with JIS K 2283:2000.
[0088] [Pour point] The pour point of the ionic liquid (A) was measured in accordance with JIS K2269:1987.
[0089] [density] The density of the ionic liquid (A) at 15° C. was measured in accordance with JIS K 2249-1:2011.
[0090] [5% mass reduction temperature)] For the ionic liquids (A-1) and (A-2), the temperatures at which the initial mass was reduced by 5% by mass (5% mass loss temperature) were measured in the same manner as for the above-mentioned corrosion inhibitor.
[0091] [Synthesis of ionic liquid (A)] Ionic liquids (A-1) and (A-2) were synthesized by the method described below.
[0092] <Ionic Liquid (A-1)> Ionic liquid (A-1): 1-butyl-1-methylpyrrolidinium-bis(trifluoromethanesulfonyl)amide 1-Methylpyrrolidine (50g, 0.587mol) and 2-propanol (70mL) were added to a 1L flask under a nitrogen atmosphere. 1-Bromobutane (96g, 0.704mol) was then added dropwise to the mixture, which was then heated to 40°C and reacted for 6 hours. After the reaction was completed, the mixture was recrystallized with ethyl acetate, and the crystals obtained by filtration were washed several times with ethyl acetate. After that, the mixture was dried at 40°C for several hours while reducing the pressure to 1mmHg or less using a vacuum pump, to obtain 1-butyl-1-methylpyrrolidinium bromide (halogenated form) (113g, 0.509mol). Next, the above halogen body (113 g, 0.509 mol) and 110 mL of pure water were prepared in a 1 L flask, and an aqueous solution of lithium bis(trifluoromethanesulfonyl)imide (151 g, 0.526 mol) dissolved in 150 mL of pure water was dropped into this. After stirring the reaction mixture at room temperature (20 ° C) for about 1 hour, it was transferred to a 1 L separatory funnel and extracted with 230 mL of methylene chloride, and the collected methylene chloride solution was washed several times with pure water. After washing, about 1 to 2 mL of the aqueous layer was collected and reacted with about 1 mL of 0.5 M silver nitrate aqueous solution to check for the presence or absence of precipitation. If a white precipitate was observed, it meant that bromide ions had not been completely removed, so washing was repeated until it was no longer visible. After completing the water washing, it was concentrated with a rotary evaporator, a small amount of activated carbon was added, and it was stirred at room temperature (20 ° C) for 1 day. This mixture was passed through a neutral alumina column and heated and stirred with a vacuum pump (60°C, 4 hours) to obtain ionic liquid (A-1). The amount of the obtained ionic liquid (A-1) was 212 g, 0.502 mol. The obtained ionic liquid (A-1) had a kinetic viscosity at 40° C. of 25.08 mm 2 / s, 100℃ kinematic viscosity: 5.662mm 2 / s, viscosity index: 177, pour point: less than −50° C., density: 1.401 (15° C.), and 5% mass loss temperature: 380° C. The structure of ionic liquid (A-1) is shown in structural formula (A-1).
[0093] [ka]
[0094] <Ionic Liquid (A-2)> Ionic liquid (A-2): 1-(2-methoxyethyl)-1-methylpyrrolidinium-bis(trifluoromethanesulfonyl)amide The same procedure was repeated as in the synthesis of ionic liquid (A-1), except that 2-iodoethyl methyl ether (131 g, 0.705 mol) was used instead of 1-bromobutane, to obtain 1-(2-methoxyethyl)-1-methylpyrrolidinium iodide (146 g, 0.538 mol). In addition, the ionic liquid (A-2) was obtained in the same manner as in the synthesis of ionic liquid (A-1), except that the obtained 1-(2-methoxyethyl)-1-methylpyrrolidinium iodide (146 g, 0.538 mol) was used instead of 1-butyl-1-methylpyrrolidinium bromide. The amount of the obtained ionic liquid (A-2) was 212 g, 0.500 mol. The obtained ionic liquid (A-2) had a kinetic viscosity at 40° C. of 21.34 mm 2 / s, 100℃ kinematic viscosity: 5.170mm 2 / s, viscosity index: 187, pour point: less than −50° C., density: 1.462 (15° C.), and 5% mass loss temperature: 388° C. The structure of ionic liquid (A-2) is shown in structural formula (A-2).
[0095] [ka]
[0096] [Preparation of Examples 1 to 6 and Comparative Examples 1 to 5] The components shown below were added in the amounts shown in Tables 2 and 3 and mixed thoroughly to obtain lubricant compositions. Details of each component used in Examples 1 to 6 and Comparative Examples 1 to 5 are as follows.
[0097] The lubricant compositions thus obtained were subjected to the following evaluations, and the results are shown in Tables 2 and 3.
[0098] [Solubility evaluation (appearance)] Three hours after preparation, the appearance of the lubricant composition was observed at 20° C. under normal pressure and rated as follows. ○: The corrosion inhibitor (B) was dissolved in the ionic liquid (A) and became colorless and transparent. ×: The corrosion inhibitor (B) did not dissolve in the ionic liquid (A).
[0099] [Low volatility evaluation (evaporation amount)] 100 g of each lubricant composition and a stirrer were placed in a flask, the pressure was reduced to 1 mmHg or less using a vacuum pump, and the mixture was stirred for 24 hours in an oil bath at 120° C. After cooling to room temperature, the mass of the remaining sample was measured, and the percentage of the reduced mass (mass%) was taken as the amount of evaporation.
[0100] [Evaluation of metal corrosion resistance] A SUS440C plate cut into a rectangular shape was immersed in a solution prepared by mixing 10 g of distilled water and 10 g of each lubricant composition. The temperature of the solution was set to 60°C, and the SUS440C plate was immersed for 7 days, after which the appearance of the SUS440C plate was observed. If brownish or black discoloration (rust) was observed on the surface, it was judged that corrosion had occurred. ○: No corrosion ×: Surface corroded
[0101] [Table 2]
[0102] [Table 3]
[0103] As can be seen from Table 2, the lubricant compositions of Examples 1 to 6, which satisfy all of the configurations of the present invention, are excellent in metal corrosion resistance, solubility, and low evaporation. Furthermore, all of the lubricant compositions of Examples 1 to 6 contain a corrosion inhibitor (B) and an ionic liquid (A) whose 5% mass loss temperature is 270° C. or higher, and therefore have excellent stability in high-temperature environments. On the other hand, as shown in Table 3, the lubricant compositions of Comparative Examples 1 and 2 did not contain the corrosion inhibitor (B), and therefore had insufficient metal corrosion resistance. In addition, in the lubricant compositions of Comparative Examples 3 and 5, the corrosion inhibitor did not dissolve in the ionic liquid, and the kinetic viscosity could not be measured. Furthermore, the lubricant composition of Comparative Example 4 had an evaporation amount exceeding 0.1 mass%, and therefore had insufficient low volatility. In addition, the lubricant compositions of Comparative Examples 4 and 5 contained a corrosion inhibitor with a 5% mass loss temperature of less than 270°C, and therefore may not be usable in the space environment, which is a high-temperature environment.
Claims
1. A compound represented by the following general formula (B1): 【Chemistry 1】 [In the general formula (B1), M represents an alkali metal, and R B11 represents an alkylene group having 3 to 19 carbon atoms.
2. A corrosion inhibitor comprising one or more compounds selected from the compounds of claim 1.
3. A lubricant composition comprising an ionic liquid (A) and the corrosion inhibitor (B) according to claim 2.
4. The lubricant composition according to claim 3 , wherein the ionic liquid (A) contains a cation represented by the following general formula (A1): 【Chemistry 2】 [In the above general formula (A1), n is 1 or 2, X is a methylene group or oxygen, and R A11 , R A12 are each independently a group selected from an ether group, an ester group, a nitrile group, and an alkyl group having 1 to 12 carbon atoms which may have a silyl group.
5. The lubricant composition according to claim 3 or 4, wherein the ionic liquid (A) comprises at least one selected from the group consisting of a compound represented by the following general formula (A2) and a compound represented by the following general formula (A3): 【Chemistry 3】 [In the above general formula (A2), n is 1 or 2, X is a methylene group or oxygen, and R A21 represents an alkyl group having 2 to 12 carbon atoms. 【Chemistry 4】 [In the above general formula (A3), n is 1 or 2, X is a methylene group or oxygen, and R A31 represents an alkylene group having 1 to 5 carbon atoms; R A32 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms.
6. The lubricant composition according to any one of claims 3 to 5, wherein the content of the compound represented by general formula (B1) is 0.1 mass % or more and 10 mass % or less, based on the total amount of the lubricant composition.
7. The lubricant composition according to any one of claims 3 to 6, wherein a ratio (B1 / A) of the content of the compound represented by general formula (B1) to the content of the ionic liquid (A) is, in mass ratio, 0.0005 or more and 0.15 or less.
Citation Information
Patent Citations
Lubricant base oil and lubricant composition
JP2012031275A
Lubricant composition excellent in anticorrosive nature making ion liquid base oil
JP2012036294A
Novel ionic liquids
WO2007147222A2